ALIH FUNGSI LAHAN DAN PERUBAHAN SOSIAL PETANI DI GORONTALO 1980-1990 - Hatu, Rauf A. (History Department, Semarang State University and Historian Society of Indonesia, 2013)
This research describes in depth about farmersÃ¢â¬â¢ social change after their farmland turned into sugar cane plantations which had an impact on the economic condition, social roles, social stratification, employment, and business opportunities among farmers of Gorontalo. The change was reflected in the increase in the labor force that moved out of agricultural sector. It also occurred in the status component in society between those who owned the land and the landless people. Landowners still had a social stratification position higher when compared to farmers who did not own any land, even those who had no land increasingly had narrower opportunities to improve their lot because they only remained becoming the farm-workers. Alternatively the government needs to implement regulations on function conversion of agricultural land which is fertile and productive because the phenomena that happen nowadays are the problems of agricultural land which start being narrowed or reduced every year.Keywords: function change, social change, farmers ÃÂ Penelitian ini mendeskripsikan secara mendalam tentang perubahan sosial petani setelah lahan pertaniannya beralih menjadi lahan perkebunan tebu yang berdampak pada kondisi ekonomi, peran sosial, stratifikasi sosial, dan kesempatan kerja serta kesempatan berusaha di kalangan petani Gorontalo. Perubahan tercermin pada terjadinya peningkatan tenaga kerja yang bergerak di luar sektor pertanian. Perubahan terjadi pula pada komponen status dalam masyarakat antara orang yang memiliki lahan dengan orang yang tidak memiliki lahan. Pemilik lahan tetap memiliki posisi stratifikasi sosial yang lebih tinggi bila dibandingkan dengan petani yang tidak memiliki lahan, bahkan orang yang tidak memiliki lahan semakin memiliki peluang yang semakin sempit dalam memperbaiki nasibnya karena hanya tetap bertahan pada buruh tani. Sebagai alternatifnya adalah pemerintah perlu menerapkan regulasi terhadap alih fungsi lahan-lahan pertanian yang subur dan produktif sebab fenomena yang terjadi sekarang ini adalah masalah lahan pertanian setiap tahun mulai menyempit atau berkurang. Kata kunci: perubahan fungsi, perubahan sosial, petani